Effectiveness of Clover Oil (Szygium Aromaticum) and Citraf Oil (Cymbopogon Citratus) as Removal of Culex Sp Mosquito Larms - Budiman; Hamidah; Maharani, Desyita (Journal of Health Literacy and Qualitative Research, 2025)
Filariasis control is carried out on a regional basis by implementing environmental management, vector control, curing or treating sufferers, providing medicine to healthy people infected with filarial worms and as a source of transmission of Filariasis as well as mass administration of preventive medicine. This study aims to evaluate the effectiveness of clove oil (Syzygium aromaticum) and lemongrass oil (Cymbopogon citratus) as natural larvicides against Culex sp mosquito larvae. The method used in conducting this research is the experimental method. Based on the research results, it shows that the results of clove leaf oil are more effective at concentrations (0.14 ml, 0.16 ml, 0.18 ml, and 0.20 ml) which can eradicate 50 Culex sp mosquito larvae with a percentage value of 50% compared to citronella oil (Cymbopogon citratus) which can only eradicate Culex sp mosquito larvae with the ability to eradicate not reaching 50 mosquito larvae. With a percentage value below 50%. It is hoped that this research can be the basis for developing natural mosquito control that is safe for the environment while supporting the prevention of vector-borne diseases in the community.